Value relevance of intangibles: A comparative analysis between financial and non-financial sector firms listed on the Argentine capital market; Relevancia valorativa de los intangibles: Análisis comparativo entre empresas del sector financiero y no financiero cotizantes en el mercado de capitales argentino - Cecilia Ficco; M. Bego\~na Prieto Moreno; Eliana Werbin; Margarita Díaz (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
The objective of this study is to analyse whether differences exist in the value relevance of intangible assets (IA) and intellectual capital (IC) between firms in the financial sector and other industries. A quantitative approach was adopted. Drawing on the work of Ohlson (1995), an original price model is constructed in the form of a specified panel data model with fixed effects. Data from to 2009- 2018, directly collected from primary sources, were used. The sample comprises 52 firms listed on the Argentine capital market without interruption throughout the period. The results show that the value relevance of IA and IC differs between non-financial and financial firms. Among the former, only the human and structural dimensions of IC were of interest to investors. In contrast, both identifiable intangible assets and the three dimensions of IC influence bank valuation, thereby confirming the importance of intangibles in this industry. The study contributes to knowledge of the impact of industry on market valuations of intangibles, which is a somewhat unexplored line of research and, likewise, to knowledge of the banking industry, a sector that has been less well studied in previous research.
Keywords: M41; G32; C33; 330; Intangible assets; intellectual capital; value relevance; industry; panel data models